Two men and a women in traditional folk attire. - Unknown:::Creator::::::::::::
Photograph shows two men and a woman wearing traditional folk attire. The man on the right has a percussion instrument in the crook of his arm and the woman has her arms around each of them with her hands on their shoulders.